2013
DOI: 10.1590/s0103-73312013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Campo comum de atuação dos profissionais da Estratégia Saúde da Família no Brasil: um cenário em construção

Abstract: Este estudo objetiva sistematizar e analisar saberes e práticas que integram o campo comum de atuação das equipes multiprofissionais da Estratégia Saúde da Família (ESF). Trata-se de estudo qualitativo, com construção das informações através de entrevistas abertas e oficinas de produção de conhecimento, com 23 profissionais da ESF e das residências médica e multiprofissional em Saúde da Família e Comunidade, no período de março a agosto de 2011, no município de Fortaleza. O campo comum é o espaço do compartilh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
1
9
0
14
Order By: Relevance
“…According to Castro et al [25], this divergence is commonly seen in the professionals given that their food choices have, in the same way, senses and meanings, and lead them to create answers to a social system which creates oppression in the name of equality, of aesthetics and health. Ellery et al [26] reinforce the importance of professionals having skills for taking care of themselves, so that this difference does not echo in their interventions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Castro et al [25], this divergence is commonly seen in the professionals given that their food choices have, in the same way, senses and meanings, and lead them to create answers to a social system which creates oppression in the name of equality, of aesthetics and health. Ellery et al [26] reinforce the importance of professionals having skills for taking care of themselves, so that this difference does not echo in their interventions.…”
Section: Discussionmentioning
confidence: 99%
“…23 Other studies addressing Nasf workers have also identified the search for a collective construction of knowledge that overcomes interdisciplinarity and becomes effective in transdisciplinarity. 10,21 Interdisciplinarity made possible through teamwork contributes to the development of new types of knowledge, adding value and pleasure to professional action, collaborating to overcome practical limitations and disciplinary views rooted in the experiences of each profession.…”
Section: Discussionmentioning
confidence: 99%
“…In the everyday reality of work in the FHS, "for an extended care to be available, it does not seem necessary nor feasible that a person or family needs to be compulsorily assisted by all kinds of practitioners of the FHS. Inter-professional work with knowledge integration and collaboration among health workers implies a certain number of shared practices, enhancing professional performance" (13) . However, from the analyzed context, it became clear that there were difficulties in sharing FHS cases under a co-responsibility perspective and understanding the NASF as a support role, as the tendency of 'passing the case' is quite common and often the responsibility for a particular health www.ee.usp.br/reeusp Analysis of suffering at work in Family Health Support Centers intervention falls on the NASF professional, similar to the findings of other authors (4,14) .…”
Section: Discussionmentioning
confidence: 99%